Village Funds, Local Politics, and the Limits of Decentralized Governance in Banten, Indonesia - Aziz Reza Randisa; Rochendi Suryadinata (Journal of Contemporary Local Politics, 2025)
This article analyzes the political dynamics and governance that shape the implementation of Indonesia's Village Fund Program based on Law No. 6 of 2014, with a focus on a qualitative case study in Banten Province. Although this program is urgent as a leading decentralization instrument that allocates significant public resources to the village level, evidence on how village governance actually operates—and why performance varies—remains uneven. Drawing on a synthesis of literature, official reports, and village-level data, this study shows that improvements in rural infrastructure and basic services go hand in hand with persistent governance deficits. Limited administrative and financial capacity among village officials, weak and procedural accountability practices, and increasingly intense local political pressures limit the democratization and development goals promoted by the law. Transparency and oversight mechanisms often function as formal compliance rather than effective control, while community participation in planning and monitoring tends to be low, facilitating patronage networks and increasing the risk of abuse of authority and corruption. The uniqueness of this article lies in its linking of decentralization outcomes to the micro-politics of village administration and the implementation of accountability. This article provides implementable policy directions such as capacity building, stronger oversight architecture, participatory guarantees, and targeted anti-corruption measures to strengthen transparency, accountability, and citizen control in the governance of Village Funds.